Excess Carrier Lifetime Improvement in c-Si Solar Cells by YAG:Ce3+-Yb3+*Supported by the Natural Science Foundation of Jiangsu Province under Grant No BK2011033. (May 2016) - Hussain, Talib; Ye 叶, Hui-Qi 慧琪; Xiao 肖, Dong 东
Abstract : Ce 3+ -Yb 3+ doped Y3 A5 O12 (YAG) is a luminescent down-conversion material which could convert visible photons to near infrared photons. In this work, YAG:Ce 3+ -Yb 3+ is applied on the front surface of mass-produced mono crystalline Si solar cells. For the coated cells, the external quantum efficiency from the visible to the near infrared is improved, and the energy conversion efficiency enhances from 11.70% to 12.2% under AM1.5G. Furthermore, the phosphor down-conversion effect on the solar cell is characterized by the microwave detected photoconductivity technique on the n-type silicon wafer under the 977nm excitation. The down-conversion materials improve the average excess carrier lifetime from 22.5 μs to 24.2 μs and the average surface recombination velocity reduces from 424.5 cm/s to 371.6 cm/s, which reveal the significant reduction in excess carrier recombination by the phosphors.